IMPLEMENTATION OF CONTEXTUAL-BASED DIFFERENTIATIONAL LEARNING ON THE PROBLEM-SOLVING ABILITY OF GRADE 8^TH STUDENTS - Iliyah, Luluk; Sari, Dwi Ivayana (Prima: Jurnal Pendidikan Matematika, 2025)
Problem-solving ability is one of the important skills in learning mathematics because it involves high-level thinking processes needed to solve complex and contextual problems. However, in reality, many students still have difficulty in understanding and solving mathematical problems because learning does not adjust to individual needs. Therefore, differentiated learning is a relevant approach because it is able to accommodate the diversity of learning styles, interests, and student readiness.This study aims to describe the application of contextual-based differentiated learning to the problem-solving abilities of grade VIII students. This study is a quantitative study with a quasi-experimental method. The research design used is a pretest-posttest control group design. Data collection techniques use observations of teachers' ability to manage learning, observations of student activities and problem-solving ability tests before and after learning. The results of the study showed that the results of observations of teachers managing learning were good because the average score was 3.00, the results of observations of student activities were 3.49, the completeness of learning outcomes in the experimental class had met the minimum completeness criteria (KKM) and the problem-solving abilities of students taught with contextual-based differentiated learning were better than the problem-solving abilities of students taught with conventional learning because the t-test showed a significant difference between the experimental and control classes (sig.0.011 <0.05), while the n-gain test showed a higher increase in problem-solving abilities in the experimental class (78.97%) compared to the control class (77.53%). This shows that contextual-based differentiated learning is more effective than conventional learning.